Chromatic Pupillometry Methods for Assessing Photoreceptor Health in Retinal and Optic Nerve Diseases - Rukmini, A. V.; Milea, Dan; Gooley, Joshua J. (Frontiers in Neurology, 2019)
The pupillary light reflex is mediated by melanopsin-containing intrinsically-photosensitive retinal ganglion cells (ipRGCs), which also receive input from rods and cones. Melanopsin-dependent pupillary light responses are short-wavelength sensitive, have a higher threshold of activation, and are much slower to activate and de-activate compared with rod/cone-mediated responses. Given that rod/cone photoreceptors and melanopsin differ in their response properties, light stimuli can be designed to stimulate preferentially each of the different photoreceptor types, providing a read-out of their function. This has given rise to chromatic pupillometry methods that aim to assess the health of outer retinal photoreceptors and ipRGCs by measuring pupillary responses to blue or red light stimuli. Here, we review different types of chromatic pupillometry protocols that have been tested in patients with retinal or optic nerve disease, including approaches that use short-duration light exposures or continuous exposure to light. Across different protocols, patients with outer retinal disease (e.g., retinitis pigmentosa or Leber congenital amaurosis) show reduced or absent pupillary responses to dim blue-light stimuli used to assess rod function, and reduced responses to moderately-bright red-light stimuli used to assess cone function. By comparison, patients with optic nerve disease (e.g., glaucoma or ischemic optic neuropathy, but not mitochondrial disease) show impaired pupillary responses during continuous exposure to bright blue-light stimuli, and a reduced post-illumination pupillary response after light offset, used to assess melanopsin function. These proof-of-concept studies demonstrate that chromatic pupillometry methods can be used to assess damage to rod/cone photoreceptors and ipRGCs. In future studies, it will be important to determine whether chromatic pupillometry methods can be used for screening and early detection of retinal and optic nerve diseases. Such methods may also prove useful for objectively evaluating the degree of recovery to ipRGC function in blind patients who undergo gene therapy or other treatments to restore vision.